Dispersion medium for sintering metal particles and conductive paste

By using an azeotropic composition of formic acid and basic compounds in conductive paste and controlling the molar ratio to 0.50–1.20, the problem of oxide film formation in metal particles in conductive paste is solved, achieving good sintering and storage stability, making it suitable for the manufacture of electronic devices.

CN115151360BActive Publication Date: 2025-01-07DAICEL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180015472.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-19
Filing Date
2021-02-02
Publication Date
2025-01-07
Estimated Expiration
2041-02-02

AI Technical Summary

Technical Problem

In existing conductive pastes, oxide films of metal particles are easily formed, leading to poor sintering and poor storage stability. Furthermore, the organic coating process is complicated, costly, and requires high-temperature reducing gas treatment.

Method used

An azeotropic composition of formic acid and a basic compound is used as a dispersion medium. The molar ratio of the basic compound to formic acid is controlled at 0.50 to 1.20 to inhibit the corrosion and agglomeration of metal particles and promote sintering.

Benefits of technology

Achieving good sintering of metal particles under an inert atmosphere improves conductivity and bonding strength, ensures storage stability, and completes sintering at low temperatures, reducing organic residues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115151360B_ABST
    Figure CN115151360B_ABST
Patent Text Reader

Abstract

The present invention provides a metal particle sintering dispersion medium that provides a conductive paste that can sinter metal particles well at low temperatures even without a reducing atmosphere, and a conductive paste using the dispersion medium. The metal particle sintering dispersion medium disclosed herein contains formic acid and a basic compound, wherein the basic compound is a nitrogen-containing compound represented by the following formula (1), and the molar ratio of the basic group contained in the basic compound to formic acid (basic group / formic acid) is 0.50 to 1.20. [Chemical Formula 1] In formula (1), R a ~R c The same or different, represents a hydrogen atom or a hydrocarbon group optionally having a substituent. A double dashed line including a dotted line represents a single bond or a double bond. In the case of a double bond, R is absent. c . R a ~R c Any two of them are optionally bonded to each other to form a ring together with the adjacent nitrogen atom.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dispersion medium for sintering metal particles and a conductive paste. This application claims priority to Japanese Patent Application No. 2020-025765 filed in Japan on February 19, 2020, the contents of which are incorporated herein by reference. Background Art

[0002] Conductive pastes are used as materials for semiconductor bonding, wire bonding, clip bonding, wiring formation, bump formation, etc. in the manufacture of electronic devices such as printed circuit boards, capacitors, inductors, varistors, thermistors, transistors, speakers, actuators, antennas, solid oxide fuel cells, and hybrid integrated circuits.

[0003] Metal particles such as copper particles used in conductive pastes tend to form an oxide film on the particle surface that hinders sintering. Therefore, conductive pastes using metal particles coated with organic matter to suppress the generation of oxide films have been studied. For example, there is a copper paste for bonding comprising copper particles coated with an organic protective agent and a dispersion medium (Patent Document 1), a conductor-forming composition comprising copper-containing particles coated with an organic matter containing an alkylamine having a hydrocarbon group with 7 or less carbon atoms, an organic acid, and a dispersion medium (Patent Document 2), etc.

[0004] However, in these conductive pastes, coating with organic matter has problems such as complicated coating steps and increased costs, and also requires high-temperature sintering to remove the coating film or the introduction of a reducing gas such as formic acid to promote sintering.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-156736

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-170228 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] In order to solve the above problems, the present inventors have tried to use an azeotropic composition containing formic acid ((formic acid / triethylamine) molar ratio: 5 / 2) as a dispersion medium capable of supplying a reducing gas (formic acid) during calcination. However, in a paste using the above azeotropic composition, a good sintered body cannot be obtained due to corrosion of metal particles, and there is also a problem that metal particles aggregate and storage stability is significantly reduced.

[0011] Therefore, the object of the present disclosure is to provide a dispersion medium for sintering metal particles, so as to eliminate the above-mentioned problems, obtain a sintered body showing good conductivity and bonding strength even when not in a reducing atmosphere, and provide a conductive paste with excellent storage stability. In addition, another object of the present disclosure is to provide a dispersion medium for sintering metal particles, wherein formic acid volatilizes in a high temperature range of 100°C or more, obtains a sintered body showing good conductivity and bonding strength even when not in a reducing atmosphere, and provides a conductive paste with excellent storage stability. In addition, another object of the present disclosure is to provide a conductive paste using the above-mentioned dispersion medium.

[0012] Technical Solution

[0013] The present inventors have conducted intensive research to solve the above technical problems and have found that when a mixture of a basic compound in a specific molar ratio with respect to formic acid is used as a dispersion medium in a conductive paste, corrosion of metal particles caused by formic acid is suppressed, a good sintered body can be achieved even without a reducing atmosphere, and aggregation of metal particles can be suppressed. The invention disclosed herein was completed based on these findings.

[0014] That is, the present disclosure provides a dispersion medium for sintering metal particles, which contains formic acid and a basic compound, wherein the basic compound is a nitrogen-containing compound represented by the following formula (1), and the molar ratio of the basic group contained in the basic compound to formic acid (basic group / formic acid) is 0.50 to 1.20.

[0015] [Chemical formula 1]

[0016]

[0017] (In formula (1), R a ~R c The same or different, represents a hydrogen atom or a hydrocarbon group optionally having a substituent. The substituents are the same or different, and are at least one group selected from amino, N-substituted amino, N,N-substituted amino, imino, N-substituted imino and hydroxyl. a ~R c A double dashed line indicates a single bond or a double bond. In the case of a double bond, R is absent. c . R a ~R c Any two of the following are optionally bonded to each other to form a ring together with the adjacent nitrogen atom)

[0018] Furthermore, the present disclosure provides a conductive paste containing metal particles and the above-mentioned dispersion medium.

[0019] Preferably, the conductive paste has a viscosity (25° C., shear rate 10 s -1 ) and the viscosity of the conductive paste obtained by a rheometer after storage at 25°C or below for 7 days (25°C, shear rate 10s -1 ) has a viscosity ratio (viscosity after storage / viscosity immediately after mixing) of 10.0 or less.

[0020] Preferably, the conductive paste has a maximum peak temperature of 100 to 220° C. in a differential thermogravimetric analysis (DTG) in a nitrogen atmosphere at a heating rate of 10° C. / min.

[0021] Preferably, the metal particles are at least one selected from copper particles, silver particles, and particles of oxides thereof.

[0022] The volume average particle size of the metal particles is preferably 1 nm or more and 100 μm or less.

[0023] Effects of the Invention

[0024] The dispersion medium disclosed in the present invention reduces the metal particles and promotes sintering even in an inert atmosphere rather than a reducing atmosphere by adding formic acid. In addition, the formic acid is neutralized and stabilized by a sufficient amount of basic groups to prevent corrosion of the metal particles and ensure the storage stability of the conductive paste. In the conductive paste disclosed in the present invention, drying is prevented by formic acid and alkaline compounds forming an azeotropic composition. In addition, the volatilization of formic acid occurs in a high temperature range of more than 100°C, thereby promoting the sintering of metal particles. In addition, after the volatilization of formic acid and alkaline compounds, the organic residue becomes very small, so a sintered body showing good conductivity even at a low temperature of about 200°C can be obtained. In addition, in the conductive paste disclosed in the present invention, high bonding strength can be obtained even at a low temperature of about 200°C and a slight pressure of less than 1MPa. DETAILED DESCRIPTION

[0025] [Dispersion medium]

[0026] The dispersion medium for sintering metal particles in the present disclosure contains formic acid and the basic compound such that the molar ratio of the basic group contained in the basic compound to formic acid (basic group / formic acid) is 0.50 to 1.20.

[0027] <Formic acid>

[0028] The formic acid in the present disclosure is compatible with the following basic compound to serve as a dispersion medium for metal particles. In addition, the formic acid reduces the oxide film on the surface of the metal particles to promote sintering of the metal particles.

[0029] In order to make the dispersion medium of the present disclosure contain formic acid in such a manner that the above-mentioned molar ratio (basic group / formic acid) is 0.50 to 1.20, formic acid or a mixed solution containing formic acid can be used. Among them, from the perspective of easy handling, a mixed solution containing 50% by weight or more of formic acid is preferred, and a formic acid-triethylamine azeotropic composition (e.g., formic acid:triethylamine=5:2 (molar ratio)), formic acid 98%, formic acid 88% aqueous solution, etc. are more preferred.

[0030] <Basic Compounds>

[0031] The basic compound in the present disclosure increases the volatilization temperature of formic acid in the conductive paste, makes the compatible substance a good dispersion medium, and suppresses corrosion of the metal particle surface caused by formic acid.

[0032] The basic compound used in the present disclosure is a nitrogen-containing compound represented by the following formula (1).

[0033] [Chemical formula 1]

[0034]

[0035] (In formula (1), R a ~R c The same or different, represents a hydrogen atom or a hydrocarbon group optionally having a substituent. The substituents are the same or different, and are at least one group selected from amino, N-substituted amino, N,N-substituted amino, imino, N-substituted imino and hydroxyl. a ~R c A double dashed line indicates a single bond or a double bond. In the case of a double bond, R is absent. c . R a ~R c Any two of the following are optionally bonded to each other to form a ring together with the adjacent nitrogen atom)

[0036] As R a ~R c Examples of the hydrocarbon group include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, and an aromatic hydrocarbon group. Among them, an aliphatic hydrocarbon group and an alicyclic hydrocarbon group are preferred, and an aliphatic hydrocarbon group is more preferred.

[0037] Examples of the aliphatic hydrocarbon group include a linear or branched alkyl group, a linear or branched alkenyl group, a linear or branched alkynyl group, and a linear or branched alkylene group. Among them, a linear or branched alkyl group is preferred.

[0038] The straight-chain or branched-chain alkyl group is preferably a straight-chain alkyl group having 1 to 12 carbon atoms, more preferably a straight-chain alkyl group having 1 to 8 carbon atoms, and further preferably a straight-chain alkyl group having 2 to 4 carbon atoms, or is preferably a branched-chain alkyl group having 3 to 12 carbon atoms, more preferably a branched-chain alkyl group having 3 to 8 carbon atoms, and further preferably a branched-chain alkyl group having 3 to 6 carbon atoms, and examples thereof include methyl, ethyl, propyl, butyl, pentyl, hexyl, decyl, dodecyl, tetradecyl, octadecyl, isopropyl, isobutyl, sec-butyl, tert-butyl, 2-ethylhexyl, and the like.

[0039] The straight-chain or branched alkenyl group is preferably a straight-chain alkenyl group having 2 to 12 carbon atoms, more preferably a straight-chain alkenyl group having 2 to 8 carbon atoms, and further preferably a straight-chain alkenyl group having 2 to 4 carbon atoms, or is preferably a branched alkenyl group having 3 to 12 carbon atoms, more preferably a branched alkenyl group having 3 to 8 carbon atoms, and further preferably a branched alkenyl group having 3 to 6 carbon atoms. Examples thereof include vinyl, 1-propenyl, 2-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-hexenyl, 3-hexenyl, 5-hexenyl, 1-heptenyl, 1-octenyl, 1-nonenyl, 1-decenyl, isopropenyl, 2-methyl-1-propenyl, methallyl, 3-methyl-2-butenyl, and 4-methyl-3-pentenyl.

[0040] The straight-chain or branched alkynyl group is preferably a straight-chain alkynyl group having 2 to 12 carbon atoms, more preferably a straight-chain alkynyl group having 2 to 8 carbon atoms, and further preferably a straight-chain alkynyl group having 2 to 4 carbon atoms, or is preferably a branched alkynyl group having 3 to 12 carbon atoms, more preferably a branched alkynyl group having 3 to 8 carbon atoms, and further preferably a branched alkynyl group having 3 to 6 carbon atoms. Examples thereof include ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, 2-pentynyl, 3-pentynyl, 4-pentynyl, 1-hexynyl, 2-hexynyl, 3-hexynyl, 4-hexynyl, 5-hexynyl, 1-heptynyl, 1-octynyl, 1-nonynyl, 1-decynyl, trimethylsilylethynyl, and triethylsilylethynyl.

[0041] The straight-chain or branched-chain alkylidene group is preferably a straight-chain alkylidene group having 1 to 12 carbon atoms, more preferably a straight-chain alkylidene group having 1 to 8 carbon atoms, and further preferably a straight-chain alkylidene group having 2 to 4 carbon atoms, or is preferably a branched-chain alkylidene group having 3 to 12 carbon atoms, more preferably a branched-chain alkylidene group having 3 to 8 carbon atoms, and further preferably a branched-chain alkylidene group having 3 to 6 carbon atoms, and examples thereof include: methylene group, propylidene group, isopropylidene group, butylidene group, isobutylidene group, sec-butylidene group, pentylidene group, isopentylidene group, octylidene group, isooctylidene group, and the like.

[0042] Examples of the alicyclic hydrocarbon group include a cycloalkyl group and a cycloalkenyl group.

[0043] The cycloalkyl group is preferably a cycloalkyl group having 3 to 12 carbon atoms, more preferably a cycloalkyl group having 4 to 10 carbon atoms, and still more preferably a cycloalkyl group having 5 to 8 carbon atoms. Examples thereof include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl.

[0044] The cycloalkenyl group is preferably a cycloalkenyl group having 3 to 12 carbon atoms, more preferably a cycloalkenyl group having 4 to 10 carbon atoms, and still more preferably a cycloalkenyl group having 5 to 8 carbon atoms, and examples thereof include a cyclopentenyl group and a cyclohexenyl group.

[0045] The aromatic hydrocarbon group is preferably an aryl group having 6 to 18 carbon atoms, more preferably an aryl group having 6 to 18 carbon atoms, and still more preferably an aryl group having 6 to 10 carbon atoms, and examples thereof include phenyl and naphthyl.

[0046] The dotted double-strike line in formula (1) represents a single bond or a double bond. When the dotted double-strike line is a double bond, R is absent. c , R in formula (1) a and R b The nitrogen atom to which it is bonded represents an imino group or an N-substituted imino group.

[0047] R a ~R c The total number of the amino group, N-substituted amino group, and N,N-substituted amino group which may be present is preferably 0 to 6, more preferably 1 to 4, and even more preferably 1 to 2.

[0048] R a ~R c The total number of the imino group and the N-substituted imino group which may be present is preferably 0 to 4, more preferably 1 to 3, and even more preferably 1 to 2.

[0049] R a ~R c The total number of the hydroxyl groups which may be present is preferably 0 to 6, more preferably 1 to 4, and even more preferably 1 to 2.

[0050] The substituents possessed by the above-mentioned N-substituted amino group, N,N-substituted amino group, and N-substituted imino group are the same as those of the above-mentioned R a ~R c The hydrocarbon groups are the same.

[0051] R a ~R cAny two of them are optionally bonded to each other to form a ring together with the adjacent nitrogen atom. Examples of the formed ring include a pyrrolidine ring, a dihydropyrrole ring, a piperidine ring, a pyrrole ring, an imidazolidine ring, an imidazole ring, a piperazine ring, an imidazolidine ring, a pyridine ring, a diazine ring, and a triazine ring.

[0052] R a ~R c The hydrocarbon group may have a substituent other than an amino group, an N-substituted amino group, an N,N-substituted amino group, an imino group, an N-substituted imino group or a hydroxyl group. Examples of such substituents include a halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom), an oxo group, a substituted oxy group (an alkoxy group having 1 to 4 carbon atoms, an aryl group having 6 to 10 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyloxy group having 7 to 16 carbon atoms, an acyloxy group having 1 to 4 carbon atoms, etc.), a carboxyl group, a substituted oxycarbonyl group (an alkoxycarbonyl group having 1 to 4 carbon atoms, an aryloxycarbonyl group having 6 to 10 carbon atoms, an aralkyloxycarbonyl group having 7 to 16 carbon atoms, etc.), a cyano group, a nitro group, a sulfo group, a mercapto group, a heterocyclic group, etc.

[0053] Specific examples of the basic compound represented by formula (1) include: a ~R c At least one of the alkylamines is a linear or branched alkyl group; R in formula (1) a , R b is a hydrogen atom, R c is a monoalkanolamine having a linear or branched alkyl group with one hydroxyl group; R in formula (1) a is a hydrogen atom, R b and R c are the same or different and are a dialkanolamine having a linear or branched alkyl group with one hydroxyl group; R in formula (1) a ~R c are the same or different and are a linear or branched alkyl trialkanolamine having one hydroxyl group; R in formula (1) a , R b are the same or different and are hydrogen atoms, linear or branched alkyl groups, R c is an aminoalkanediol having a linear or branched alkyl group with two hydroxyl groups; R in formula (1) a ~R c is a diamine having a total number of amino groups of 1; R in formula (1) a ~R c is a triamine having a total number of amino groups of 2; R in formula (1) a ~R cis a diaminoalkanol having a total of 1 amino group and a total of 1 hydroxyl group; R in formula (1) a ~R c An imidazole compound containing 1 imino group in total, which forms a ring including the nitrogen atom of the imino group; R in formula (1) a , R b The nitrogen atom to be bonded is an imino group, and a nitrogen-containing aromatic compound (a pyridine compound, a diazine compound, a triazine compound, etc.) that forms a ring including the imino group, etc.

[0054] Examples of the alkylamine include methylamine, ethylamine, propylamine, butylamine, pentylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dipentylamine, piperidine, trimethylamine, triethylamine, 4-dimethylaminopyridine, 2-aminopyrazine, 2-aminopyrimidine, 3-aminopyridazine, 2-aminotriazine, diazabicyclononene, and diazabicycloundecene.

[0055] Examples of the monoalkanolamine include 2-aminoethanol, 3-aminopropanol, 1-amino-2-propanol, 1-amino-2-methyl-2-propanol, 2-amino-2-methyl-1-propanol, 4-amino-1-butanol, 6-amino-1-hexanol, 10-amino-1-decanol, 12-amino-1-dodecanol, N-methyl-2-aminoethanol, N-ethyl-2-aminoethanol, N-propyl-2-aminoethanol, 2-dimethylaminoethanol, 6-diethylaminohexanol, 1-(2-hydroxyethyl)pyrrolidine, 2-(hydroxymethyl)pyrrolidine, 2-(2-hydroxyethyl)-1-methylpyrrolidine, 1-piperidineethanol, and 1-ethanol-4-propanolpiperidine.

[0056] As said dialkanolamine, a diethanolamine, a di-n-propanolamine, a diisopropanolamine, a di-n-butanolamine, a diisobutanolamine etc. are mentioned, for example.

[0057] As said trialkanolamine, triethanolamine, tri-n-propanolamine, triisopropanolamine, tri-n-butanolamine, triisobutanolamine etc. are mentioned, for example.

[0058] Examples of the aminoalkanediol include 1-amino-2,3-propanediol, 4-amino-1,2-butanediol, 4-amino-1,3-butanediol, 2-amino-1,3-propanediol, 2-amino-2-methyl-1,3-propanediol, 1-methylamino-2,3-propanediol, 1-ethylamino-2,3-propanediol, 1-propylamino-2,3-propanediol, 1-butylamino-2,3-propanediol, 3-dimethylamino-1,2-propanediol, and 2-diethylamino-1,3-propanediol.

[0059] Examples of the diamines include 1,3-propylenediamine, 2,2-dimethyl-1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,5-diamino-2-methylpentane, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyl-1,3-propylenediamine, N,N'-diethyl-1,3-propylenediamine, N,N'-dimethyl-1,4-butylenediamine, N,N'-diethyl-1,4-butylenediamine, N,N'- dimethyl-1,6-hexanediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dimethyl-1,3-propylenediamine, N,N-diethyl-1,3-propylenediamine (=diethylaminopropylamine), N,N-dimethyl-1,4-butanediamine, N,N-diethyl-1,4-butanediamine, N,N-dimethyl-1,6-hexanediamine, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, piperazine, N-methylpiperazine, N-ethylpiperazine, N,N'-dimethylpiperazine, homopiperazine, and the like.

[0060] Examples of the triamine include diethylenetriamine, N,N,N',N",N"-pentamethyldiethylenetriamine (=pentamethyldiethylenetriamine), N,N,N',N",N"-penta(2-hydroxypropyl)diethylenetriamine, 3,3'-diaminodipropylamine, N-(3-aminopropyl)-N-methyl-1,3-propanediamine, N'-[3-(dimethylamino)propyl]-N,N-dimethyl-1,3-propanediamine, 2,6,10-trimethyl-2,6,10-triazaundecane, N-(2-aminoethyl)piperazine, 1,4,7-triazacyclononane, N,N,N',N",N"-penta(2-hydroxypropyl)diethylenetriamine, 1-(2-aminoethyl)-4-methylpiperazine, and 1-(2-dimethylaminoethyl)-4-methylpiperazine.

[0061] Examples of the diaminoalkanol include 1,3-diaminopropane-2-ol, 2-(2-aminoethylamino)ethanol, 2-(2-aminopropylamino)ethanol, 2-(2-aminoethylmethylamino)ethanol, 1-(2-hydroxyethyl)piperazine, 4-methylpiperazine-1-ethanol, and 1,4-bis(2-hydroxyethyl)piperazine.

[0062] Examples of the imidazole compound include imidazole, 2-methylimidazole, 2-propylimidazole, N-methylimidazole (=1-methylimidazole), N-propylimidazole, N-butylimidazole, 1-(2-hydroxyethyl)imidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 1-acetylimidazole, and 2-hydroxybenzimidazole.

[0063] Examples of the nitrogen-containing aromatic compound include pyridine, α-methylpyridine, β-methylpyridine, γ-methylpyridine, 2,6-lutidine, 2,3-lutidine, pyrazine, 2-hydroxypyrazine, pyrimidine, 2-hydroxypyrimidine, 4-hydroxypyrimidine, pyridazine, 3-hydroxypyridazine, 4-hydroxypyridazine, triazine, and 2-hydroxytriazine.

[0064] These can be used alone or in combination of two or more.

[0065] The above-mentioned basic compound can be liquid or solid at normal temperature and pressure.

[0066] The dispersion medium disclosed herein is a mixture containing formic acid and the above-mentioned basic compound, and is liquid or solid at normal temperature and pressure, but is preferably an organic substance that becomes liquid when mixed with metal particles and can disperse the metal particles to form a paste.

[0067] The molar ratio of the number of moles of the basic group of the above-mentioned basic compound to the number of moles of formic acid in the dispersion medium of the present invention (basic group / formic acid) is preferably 0.50 to 1.20, more preferably 0.55 to 1.15, and further preferably 0.60 to 1.10. When the molar ratio is lower than 0.50, there is a tendency for the storage stability of the conductive paste to deteriorate, and when it exceeds 1.20, there is a tendency for it to be difficult to obtain a sintered body showing good conductivity. It should be noted that the number of moles of the basic group of the basic compound refers to the value obtained by multiplying the number of moles of the basic compound by the number of basic groups possessed by the basic compound, and the basic group in the above-mentioned imidazole compound refers to the basic group associated with the nitrogen atom at the 1-position.

[0068] In order to adjust the fluidity (viscosity) and workability, the dispersion medium of the present disclosure may contain: an organic solvent other than water or a mixture of formic acid and the above-mentioned basic compound (for example, organic acids other than formic acid (acetic acid, propionic acid, octanoic acid, etc.); ester solvents such as acetates (ethyl acetate, butyl acetate, etc.); ether solvents such as dioxane and tetrahydrofuran; ketone solvents such as acetone; aromatic solvents such as toluene and xylene; halogen solvents such as dichloromethane and chloroform; alcohol solvents such as methanol, ethanol, isopropanol, butanol; nitrile solvents such as acetonitrile and benzonitrile, etc.), a resin component (for example, a polymer compound having a number average molecular weight of 10,000 or more such as ethyl cellulose resin, alkyl cellulose resin, polyvinyl acetal resin, acrylic resin), a basic compound other than the above-mentioned basic compound (inorganic bases (sodium hydroxide, potassium hydroxide, ammonia, etc.)), additives (surface adjusters (leveling agents), defoamers, dispersants, thixotropy imparting agents, etc.), etc.

[0069] The dispersion medium of the present disclosure can be produced through a step of mixing the formic acid and the basic compound described above with other components to make them compatible.

[0070] The temperature during mixing is preferably not more than 100°C.

[0071] The cooling after mixing may be performed to room temperature (eg, 25° C.) or lower, and may be performed slowly at room temperature or rapidly by ice cooling or the like.

[0072] [Conductive paste]

[0073] The conductive paste disclosed herein contains metal particles and a dispersion medium containing formic acid and an alkaline compound, and can be suitably used as a material for semiconductor bonding, wire bonding, clamp bonding, wiring formation, bump formation, etc., and can be used in the manufacture of electronic devices (printed circuit boards, capacitors, inductors, varistors, thermistors, transistors, speakers, actuators, antennas, solid oxide fuel cells, hybrid integrated circuits, etc.).

[0074] <Metal Particles>

[0075] The metal particles used in the present disclosure may be particles of metals having conductivity after sintering, and examples thereof include particles of gold, silver, copper, nickel, palladium, tin, aluminum, or alloys thereof, or oxides thereof (copper oxide (Cu2O, CuO)), silver oxide, etc.). Among them, from the perspective of obtaining a sintered body having high conductivity, at least one selected from copper particles, silver particles, and particles of oxides thereof is preferred, copper particles and / or silver particles are more preferred, and copper particles are further preferred.

[0076] These may be used alone or in combination of two or more.

[0077] The metal particles may be in various shapes such as spherical, ellipsoidal, flake (flat), fibrous, etc., or in irregular shapes, but are preferably spherical or flake in terms of coating properties and storage stability of the conductive paste. They may be used alone or in combination of two or more.

[0078] The volume average particle size (median diameter, D 50 ) is preferably 1 nm to 100 μm, more preferably 10 nm to 50 μm, further preferably 30 nm to 35 μm, particularly preferably 50 nm to 10 μm, and most preferably 70 nm to 1 μm.

[0079] In addition, the metal particles may be used in combination with two or more metal particles having different volume average particle diameters, such as nano-sized particles having a volume average particle diameter of preferably 1 nm or more and less than 300 nm, more preferably 1 to 200 nm, and further preferably 1 to 150 nm; sub-nano-sized particles having a volume average particle diameter of preferably 0.30 μm or more and less than 1.00 μm, more preferably 0.40 to 0.95 μm, and further preferably 0.50 to 0.90 μm; and micron-sized particles having a volume average particle diameter of preferably 1.0 to 100 μm, more preferably 1.5 to 50 μm, further preferably 2.0 to 35 μm, particularly preferably 2.5 to 10 μm, and most preferably 3.0 to 10 μm. The volume average particle diameter of the metal particles may be measured, for example, using a commercially available laser particle size distribution meter (e.g., SALD-7000 manufactured by Shimadzu Corporation).

[0080] When metal particles having different volume average particle sizes are used together, the weight ratio of the nanosized particles in the entire metal particles (nanosized particles / entire metal particles) is preferably 0.10 to 0.90, more preferably 0.15 to 0.85, and even more preferably 0.20 to 0.80.

[0081] When metal particles of two or more metals are used in combination, the weight ratio of copper particles in the entire metal particles (copper particles / total metal particles) is preferably 0.35 to 0.90, more preferably 0.40 to 0.87, and even more preferably 0.45 to 0.84.

[0082] The content of the above-mentioned metal particles in the conductive paste of the present disclosure (the total when containing metal particles of two or more metals and / or two or more particle sizes) is preferably 70 to 99% by weight, more preferably 72 to 95% by weight, further preferably 74 to 93% by weight, particularly preferably 76 to 95% by weight, and most preferably 78 to 93% by weight.

[0083] In the conductive paste of the present invention, from the perspective of easily obtaining a sintered body showing good conductivity, the content of formic acid, the content of the above-mentioned alkaline compound, and the weight ratio (alkaline compound / formic acid) preferably satisfy the following ranges at the same time. The content of formic acid is preferably 4.0 to 8.9% by weight, more preferably 4.3 to 8.0% by weight, and further preferably 4.5 to 7.5% by weight. The content of the above-mentioned alkaline compound (the total content when two or more are used in combination) is preferably 6.5 to 12.0% by weight, more preferably 6.6 to 11.8% by weight, and further preferably 6.7 to 11.5% by weight. Moreover, the weight ratio of the above-mentioned alkaline compound to formic acid (alkaline compound / formic acid) is preferably 0.70 to 3.50, more preferably 0.72 to 3.40, and further preferably 0.74 to 3.30.

[0084] In order to suppress the collapse and flow of the conductive paste after coating and improve the coating accuracy, and to stably maintain the uniform dispersion state of the metal particles, the viscosity (25° C., shear rate 10 s -1 ) is preferably 10 to 1000 Pa·s, more preferably 50 to 900 Pa·s, and further preferably 100 to 800 Pa·s.

[0085] The conductive paste of the present disclosure exhibits excellent storage stability at, for example, -50°C to 30°C. The viscosity (25°C, shear rate 10s -1 ) is preferably 4 to 10000 Pa·s, more preferably 20 to 4500 Pa·s, and even more preferably 50 to 2400 Pa·s. It should be noted that the above viscosity can be measured by the method described in the Examples.

[0086] In the conductive paste of the present disclosure, the viscosity (25° C., shear rate 10 s -1 ) and the viscosity of the conductive paste obtained by a rheometer after storage at 25°C or below (e.g., 25°C, 5°C) for 7 days (25°C, shear rate 10s -1 ) is preferably 10.0 or less, more preferably 0.4 to 5.0, and even more preferably 0.5 to 3.0.

[0087] The reason why excellent storage stability is obtained by blending the basic compound is not clear, but it is presumed that the reason is that formic acid is stabilized and the formic acid is prevented from reacting with the metal particles to form aggregates.

[0088] The temperature at which the slope of the weight loss in the thermogravimetric analysis TG (temperature increase rate 10°C / min, under nitrogen atmosphere) of the conductive paste disclosed herein is the maximum, i.e., the maximum peak temperature of the differential thermogravimetric analysis (DTG) is preferably 100 to 220°C, more preferably 110 to 210°C, and further preferably 120 to 200°C. When the peak temperature is lower than 100°C, formic acid volatilizes too quickly, and there is a tendency that the reduction of the metal particles becomes insufficient, and when it exceeds 220°C, there is a tendency that the entire dispersion medium remains and the low-temperature sintering is easily hindered.

[0089] The conductive paste of the present disclosure can be produced by mixing the metal particles with the above-mentioned dispersion medium. In addition, the conductive paste of the present disclosure can be produced by mixing the metal particles with the above-mentioned formic acid, alkaline compound and other components.

[0090] The temperature during mixing is preferably not more than 100°C.

[0091] The cooling after mixing may be performed to room temperature (eg, 25° C.) or lower, and may be performed slowly at room temperature or rapidly by ice cooling or the like.

[0092] The total content of the organic solvent other than water, formic acid and the mixture of the above-mentioned basic compounds, the basic compounds other than the above-mentioned basic compounds, additives, and the like in the conductive paste of the present disclosure is preferably 10% by weight or less.

[0093] The conductive paste disclosed in the present invention has a moderate viscosity as described above, so no resin component may be added. Even when a resin component is added, the content of the resin component in the conductive paste is preferably 10% by weight or less, and more preferably 5% by weight or less. If the amount of the resin component added exceeds the above range, the electrical properties are reduced due to the ash derived from the resin component generated by firing, so it is not preferred.

[0094] The mixture of formic acid and the above-mentioned alkaline compound contained in the conductive paste of the present invention volatilizes rapidly during firing, and the formic acid oxidizes and reduces the surface of the metal particles. Therefore, even if it is not in a reducing atmosphere, the conductive paste can be fired at a low temperature (preferably 120 to 320°C, more preferably 150 to 290°C, and further preferably 180 to 260°C).

[0095] The conductive paste disclosed in the present invention has the above-mentioned characteristics, so it can be well discharged onto the surface of a substrate (e.g., a ceramic substrate, a printed circuit board (green sheet), etc.) by, for example, screen printing, and can make the edge of the drawing part clearer and improve the printing accuracy. In addition, it can prevent the sedimentation and local aggregation of metal particles, stably maintain a uniform and highly dispersed state and perform discharge and printing, and by drying and firing the discharged conductive paste, it can form wiring with good conductivity with good accuracy.

[0096] In addition, the conductive paste of the present disclosure can be selectively discharged to a desired position on the surface of a substrate provided with electrodes, circuits, etc., for example, by screen printing, and then the electronic components, etc. are bonded and fired, thereby electrically connecting the substrate and the electronic components, etc. In addition, since firing can be performed at a low temperature, it can be mounted at a low temperature compared to mounting using solder, and can be used to mount electronic components that lack heat resistance, etc.

[0097] Therefore, the conductive paste of the present invention is particularly useful in the manufacture of printed circuit boards such as multilayer printed circuit boards, capacitors such as laminated ceramic capacitors, inductors, varistors, thermistors, transistors, speakers, actuators, antennas, solid oxide fuel cells (SOFCs), hybrid integrated circuits, and the like, especially laminated ceramic capacitors.

[0098] Each configuration and combination thereof in the above-mentioned embodiments are examples, and addition, omission, substitution, and other changes of configurations may be appropriately made without departing from the gist of the present disclosure. The present disclosure is not limited by the embodiments but only by the claims.

[0099] Example

[0100] Hereinafter, the present disclosure will be described in more detail based on examples, but the present disclosure is not limited to these examples.

[0101] In the following, unless otherwise specified, the volume average particle size (median diameter, D 50 ) is a value measured by laser diffraction / scattering method.

[0102] The metal particles (copper particles, silver particles, copper oxide), solvents (formic acid, alkaline compounds, organic solvents, organic acids other than formic acid), and additives used are shown below.

[0103] <Copper particles>

[0104] TNCu: volume average particle size 110 nm (calculated based on SEM observation), manufactured by Taiyo Nippon Sanso Co., Ltd.

[0105] 1200YP: volume average particle size 3.1 μm, manufactured by Mitsui Mining & Smelting Co., Ltd.

[0106] CT-0500: volume average particle size 0.74 μm, manufactured by Mitsui Mining & Smelting Co., Ltd.

[0107] 1050Y, volume average particle size 0.81 μm, manufactured by Mitsui Mining & Smelting Co., Ltd.

[0108] <Silver particles>

[0109] S211A-10: volume average particle size: 0.54 μm, manufactured by Daiken Chemical Industry Co., Ltd.

[0110] <Copper Oxide>

[0111] Cu2O: Copper (I) oxide 99.5%, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.

[0112] CuO: copper (II) oxide powder, manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.

[0113] <Formic acid>

[0114] · Formic acid 88% aqueous solution: manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.

[0115] Formic acid / triethylamine (5:2 molar ratio azeotropic composition): manufactured by Tokyo Chemical Industry Co., Ltd.

[0116] <Basic Compounds>

[0117] · Triethanolamine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0118] 1-Methylimidazole: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0119] Pentamethyldiethylenetriamine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0120] · N-Ethyldiethanolamine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0121] ·Diethanolamine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0122] Diethylaminopropylamine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0123] · N,N'-Dimethylpiperazine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0124] 1-(2-Dimethylaminoethyl)-4-methylpiperazine: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0125] <Organic Solvents>

[0126] · Triethylene glycol: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0127] <Organic acids other than formic acid>

[0128] Acetic acid: a reagent manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.

[0129] · Octanoic acid: a reagent manufactured by Tokyo Chemical Industry Co., Ltd.

[0130] <Additives>

[0131] BYK-067A: Silicone defoamer, manufactured by BYK Additives & Instruments. [Peak temperature at which the slope of weight loss is maximum (DTG maximum peak temperature)]

[0132] Using a thermogravimetric analyzer (TG-DSC STA200 manufactured by Hitachi Hightech Science Co., Ltd.), the TG curve measured by thermogravimetric measurement under a nitrogen atmosphere (flow rate 200 ml / min) and a heating rate of 10°C / min was differentiated. For the obtained differential thermogravimetric (DTG) curve, the peak with the largest value in the negative direction was taken as the DTG maximum peak.

[0133] [Storage stability evaluation]

[0134] The storage stability evaluation of the conductive paste was performed as follows: for the storage stability evaluation samples stored in the atmosphere at room temperature (25°C) or 5°C for one or two weeks, a rheometer (MCR302, manufactured by Anton Paar) was used, the measuring fixture was PP12, the gap was set to 0.05 mm, and the shear rate was changed from 0.01 to 1000 s on a logarithmic scale at 25°C. -1 The viscosity curve is obtained, and the shear rate 10s is calculated based on the obtained viscosity curve. -1 The initial viscosity just after mixing (B0), the viscosity after storage at 25°C for one week (B1), the viscosity after storage at 25°C for two weeks (B2), the viscosity after storage at 5°C for one week (B3), and the viscosity after storage at 5°C for two weeks (B4) were compared.

[0135] (Example 1)

[0136] A formic acid / triethylamine mixed solvent (a 5:2 molar ratio azeotropic composition), triethanolamine, and TNCu were mixed in the amounts shown in Table 1, and stirred for five minutes using a rotary-revolution stirrer (THINKY MIXER, manufactured by THINKY Co., Ltd.). The molar ratio of formic acid to basic group (basic group / formic acid) was 0.96. The DTG maximum peak temperature was 130°C. For the viscosity B1 to B4 of the paste of Example 1 after storage, the viscosity ratios B1 / B0, B2 / B0, B3 / B0, and B4 / B0 were all less than 1, showing good storage stability.

[0137] (Comparative Example 1)

[0138] A paste was prepared in the same manner as in Example 1 for the blending ratios not containing triethanolamine as described in Table 1. The paste of Comparative Example 1 had aggregates formed inside the paste during storage, making it difficult to measure the viscosity, and exhibited poor storage stability. The DTG maximum peak temperature was 123°C.

[0139] (Example 2)

[0140] A 88% aqueous solution of formic acid, 1-methylimidazole, and TNCu were mixed in the amounts shown in Table 1, and a paste was prepared in the same manner as in Example 1. The molar ratio of formic acid to basic group was 0.61. The DTG maximum peak temperature was 135° C. For the viscosity B1 to B4 of the paste of Example 2 after storage, when the viscosity ratios B1 / B0, B2 / B0, and B4 / B0 were less than 1 and B3 / B0 was 1.09, good storage stability was shown.

[0141] (Comparative Example 2)

[0142] As described in Table 1, the mixing ratio of 1-methylimidazole was reduced compared with Example 2, and a paste was prepared in the same manner as in Example 1. The molar ratio of formic acid to basic group was 0.40. The paste of Comparative Example 2, like the paste of Comparative Example 1, had aggregates generated inside the paste during storage, making it difficult to measure the viscosity, showing poor storage stability. The DTG maximum peak temperature was 117°C.

[0143] [Table 1]

[0144]

[0145] [Evaluation of electrical conductivity]

[0146] The conductivity of the conductive paste was evaluated as follows: a film of the conductive paste having a thickness of 25 μm was formed by applying the conductive paste on a slide glass masked on all sides with a masking tape (polyester film tape 631U#12, manufactured by Teraoka Seisakusho Co., Ltd.) using a squeegee, and the film was sintered in a nitrogen atmosphere using a sintering furnace (RSS-450-210-FA, manufactured by UNITEMP) at the sintering temperature and sintering time described in Table 2. The volume resistivity of the sample for conductivity evaluation thus obtained was measured using a resistivity meter (Loresta GP MCP-T610, manufactured by Mitsubishi Chemical Analytech Co., Ltd.).

[0147] (Examples 1 and 2)

[0148] The pastes of Examples 1 and 2 both showed good conductivity with a volumetric efficiency of 100 μΩ·cm or less. The paste of Example 2 also showed good conductivity even when sintered at a low temperature of 200°C.

[0149] (Examples 3 and 4)

[0150] A paste was prepared in the same manner as in Example 1 by mixing formic acid 88% aqueous solution, triethanolamine and TNCu in the contents shown in Table 2. The molar ratios of formic acid to basic group were 1.00 and 0.60, respectively. The DTG maximum peak temperatures were 192° C. and 132° C., respectively. The pastes of Examples 3 and 4 both showed good conductivity.

[0151] (Examples 5 to 7)

[0152] A paste obtained by blending a formic acid 88% aqueous solution, pentaethylenetriamine as a polyfunctional amine, and TNCu in the contents described in Table 2 in the same manner as in Example 1 also exhibited good conductivity.

[0153] (Example 8)

[0154] A paste obtained in the same manner as in Example 1 by blending a 88% aqueous formic acid solution, diethanolamine, and TNCu in the amounts shown in Table 2 also exhibited good conductivity. The DTG maximum peak temperature was 133°C.

[0155] (Example 9)

[0156] A paste obtained in the same manner as in Example 1 by blending a 88% aqueous solution of formic acid, diethylaminopropylamine, and TNCu in the amounts shown in Table 2 also exhibited good conductivity. The DTG maximum peak temperature was 129°C.

[0157] (Examples 10 to 13)

[0158] A paste obtained in the same manner as in Example 1 by mixing an 88% aqueous formic acid solution, two basic compounds, 1-methylimidazole and N-ethyldiethanolamine, and TNCu in the ratio described in Table 2 also exhibited good conductivity. In Example 10, the maximum DTG peak temperature was 131°C.

[0159] (Comparative Example 3)

[0160] A paste was prepared in the same manner as in Example 1 by mixing an 88% aqueous solution of formic acid, two alkali compounds used in combination, 1-methylimidazole and N-ethyldiethanolamine, and TNCu in the ratio shown in Table 2 so that the molar ratio of formic acid to alkali was 1.31. The paste of Comparative Example 3 had a volume resistivity of 377 μΩ·cm, indicating poor conductivity. The DTG maximum peak temperature was 136°C.

[0161]

[0162] For the DTG maximum peak temperature in Table 2, “-” means not measured.

[0163] (Example 14)

[0164] A paste was prepared in the same manner as in Example 1 by blending formic acid, n-octanoic acid, pentamethyldiethylenetriamine, and TNCu in the contents shown in Table 3. The paste of Example 14 had a volume resistivity of 11 μΩ·cm, indicating good conductivity.

[0165] (Example 15)

[0166] A paste obtained in the same manner as in Example 1 in which formic acid, pentamethyldiethylenetriamine, triethylene glycol as another organic solvent, and TNCu were blended in the contents described in Table 3 also exhibited good conductivity.

[0167] (Comparative Example 4)

[0168] A paste was prepared in the same manner as in Example 1, except that formic acid was not added and 1-methylimidazole, diethanolethylamine and TNCu were added in the amounts shown in Table 3. The volume resistivity of the paste of Comparative Example 4 was very high, 6020 μΩ·cm, and unlike Example 13 (Table 2), it showed very poor conductivity.

[0169] (Comparative Examples 5 and 6)

[0170] Acetic acid or n-octanoic acid, pentamethyldiethylenetriamine, and TNCu as organic acids other than formic acid were blended in the contents described in Table 3, and pastes were prepared in the same manner as in Example 1. The paste samples of Comparative Examples 5 and 6 did not show conductivity.

[0171] [Table 3]

[0172]

[0173] (Example 16)

[0174] The paste was prepared in the same manner as in Example 2 (TNCu: copper nanoparticles, average particle size 110 nm) except that 1200YP (copper flake particles, average particle size 3.1 μm) was used as metal particles. The volume resistivity of the paste of Example 16 was 46 μΩ·cm, and similarly to the paste of Example 2, it exhibited good conductivity.

[0175] (Examples 17 and 18)

[0176] The pastes were prepared in the same manner as in Example 2 except that CT-0500 (copper submicron particles, average particle size 0.74 μm) or 1050Y (copper submicron particles, average particle size 0.81 μm) was used as metal particles. The volume resistivities of the pastes of Examples 17 and 18 were 84 μΩ·cm and 64 μΩ·cm, respectively, and they exhibited good conductivity similarly to the paste of Example 2.

[0177] (Examples 19 to 35)

[0178] Except for using a mixture of TNCu and 1200YP, TNCu and CT-0500, and TNCu and 1050Y in the contents described in Table 4 as metal particles, the pastes obtained in the same manner as in Example 2 all showed good conductivity.

[0179] (Example 36)

[0180] The paste obtained in the same manner as in Example 7 showed good conductivity except that a mixture of TNCu and S211A-10 (silver submicron particles, average particle size 0.54 μm) was used as metal particles in the contents described in Table 4.

[0181] (Examples 37 and 38)

[0182] The paste obtained in the same manner as in Example 2 showed good conductivity except that a mixture of TNCu and cuprous oxide (Cu2O) or copper oxide (CuO) as a metal compound was used in the amounts shown in Table 4 as metal particles.

[0183]

[0184] [Joining performance evaluation]

[0185] The bonding performance evaluation was conducted on the pastes of Examples 1, 5, 13, 15, and Example 39 having the same composition as that of Example 5 but further blending BYK-067A as an additive.

[0186] The evaluation of the bonding performance of the conductive paste is carried out as follows: for the material obtained by forming a conductive paste on a copper substrate (oxygen-free copper plate, 14 mm × 9 mm × 1 mm, manufactured by Asahi Manufacturing Co., Ltd.) using a metal mask printing method (metal mask: 4 mm × 4 mm, mesh thickness 100 μm, manufactured by Towa Tech Co., Ltd.), a copper dummy chip (dummy chip) (oxygen-free copper plate, 14 mm × 9 mm × 1 mm, manufactured by Asahi Manufacturing Co., Ltd.) is placed on the coating film (coating film thickness: about 100 μm), and the material is pressurized in a nitrogen atmosphere by the same method as International Publication No. WO2018 / 029983, and the temperature is increased from room temperature 25°C to 300°C, 250°C, 200°C or 180°C at a heating rate of 20°C / min, and then further heated for 30 minutes. For the bonding performance evaluation sample (copper substrate / sintered conductive paste / copper dummy chip) obtained in this way, a chip shear tester (Die The bonding strength was measured using Shear Tester (SERIES 4000, manufactured by DAGE) at room temperature, a test speed of 50 μm / s, and a test height of 50 μm.

[0187] In all cases of Examples 1, 5, 13, 15, and 39, the bonding strength exceeded 20 MPa, showing good bonding performance. It is shown that the conductive paste formulated with formic acid and alkali can be used in bonding. In addition, in Examples 5 and 39, the bonding strength exceeded 20 MPa even at extremely low sintering temperatures such as 200°C and 180°C, showing good bonding performance. In addition, in Example 39, by formulating an additive such as BYK-067A, the bonding strength exceeded 20 MPa even when sintering was performed without pressurization or at an extremely low pressurization pressure such as 0.05 MPa, showing good bonding performance.

[0188]

[0189] As a summary of the above, the configuration of the present disclosure and its variations are described below.

[0190] [1] A dispersion medium for sintering metal particles, comprising formic acid and a basic compound, wherein the basic compound is a nitrogen-containing compound represented by formula (1), and the molar ratio of a basic group contained in the basic compound to formic acid (basic group / formic acid) is 0.50 to 1.20.

[0191] [2] The metal particle sintering dispersion medium according to [1], wherein R in the formula (1)a ~R c It is an aliphatic hydrocarbon group.

[0192] [3] The dispersion medium for sintering metal particles according to [2], wherein the aliphatic hydrocarbon group is a linear or branched alkyl group.

[0193] [4] The dispersion medium for sintering metal particles according to [2], wherein the aliphatic hydrocarbon group is a linear alkyl group having 2 to 12 carbon atoms (preferably 2 to 8, more preferably 2 to 4) or a branched alkyl group having 3 to 12 carbon atoms (preferably 3 to 8, more preferably 3 to 6).

[0194] [5] The metal particle sintering dispersion medium according to any one of [1] to [4], wherein R in the formula (1) a ~R c The total number of the amino group, N-substituted amino group or N,N-substituted amino group which may be present is 0 to 6 (preferably 1 to 4, more preferably 1 to 2).

[0195] [6] The metal particle sintering dispersion medium according to any one of [1] to [5], wherein R in the formula (1) a ~R c The total number of the imino group or N-substituted imino group which may be present is 0 to 4 (preferably 1 to 3, more preferably 1 to 2).

[0196] [7] The metal particle sintering dispersion medium according to any one of [1] to [6], wherein R in the formula (1) a ~R c The total number of the hydroxyl groups which may be present is 0 to 6 (preferably 1 to 4, more preferably 1 to 2).

[0197] [8] The metal particle sintering dispersion medium according to [2], wherein R in the formula (1) a ~R c Any two of the rings optionally bonded to each other and formed together with the adjacent nitrogen atom are at least one selected from a pyrrolidine ring, a dihydropyrrole ring, a piperidine ring, a pyrrole ring, an imidazolidine ring, an imidazole ring, a piperazine ring, an imidazolidine ring, a pyridine ring, a diazine ring and a triazine ring.

[0198] [9] The dispersion medium for sintering metal particles according to [8], wherein the ring is an imidazole ring.

[0199]

[10] The dispersion medium for sintering metal particles according to [1], wherein the alkaline compound is at least one compound selected from alkylamines, dialkanolamines, trialkanolamines, aminoalkanediols, diamines, triamines, diaminoalkanols, imidazole compounds, pyridine compounds, diazine compounds and triazine compounds.

[0200]

[11] The dispersion medium for sintering metal particles according to [1], wherein the basic compound is at least one compound selected from alkylamines, dialkanolamines, trialkanolamines, diamines, triamines, diaminoalkanols and imidazole compounds.

[0201]

[12] A dispersion medium for sintering metal particles according to [1], wherein the alkaline compound is at least one compound selected from triethylamine, diethanolamine, triethanolamine, N,N-diethyl-1,3-propylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N'-dimethylpiperazine, 1-(2-aminoethyl)-4-methylpiperazine and N-methylimidazole.

[0202]

[13] The metal particle sintering dispersion medium according to any one of [1] to

[12] , wherein the molar ratio (basic group / formic acid) is 0.55 to 1.15 (preferably 0.60 to 1.10).

[0203]

[14] A method for producing a dispersion medium for sintering metal particles, which is the method for producing a dispersion medium for sintering metal particles described in any one of [1] to

[13] , the method comprising the step of mixing the formic acid and the basic compound to make them compatible.

[0204]

[15] A conductive paste comprising metal particles and the dispersion medium according to any one of [1] to

[13] .

[0205]

[16] The conductive paste according to

[15] , wherein the viscosity (25° C., shear rate 10 s -1 ) is 10 to 1000 Pa·s (preferably 50 to 900 Pa·s, more preferably 100 to 800 Pa·s).

[0206]

[17] The conductive paste according to

[15] or

[16] , wherein the viscosity (25°C, shear rate 10 s -1 ) is 4 to 10000 Pa·s (preferably 20 to 4500 Pa·s, more preferably 50 to 2400 Pa·s).

[0207]

[18] The conductive paste according to any one of

[15] to

[17] , wherein the viscosity (25°C, shear rate 10 s -1 ) is 4 to 10000 Pa·s (preferably 20 to 4500 Pa·s, more preferably 50 to 2400 Pa·s).

[0208]

[19] The conductive paste according to any one of

[15] to

[18] , wherein the viscosity (25°C, shear rate 10 s -1 ) is 4 to 10000 Pa·s (preferably 20 to 4500 Pa·s, more preferably 50 to 2400 Pa·s).

[0209]

[20] The conductive paste according to any one of

[15] to

[19] , wherein the viscosity (25°C, shear rate 10 s -1 ) is 4 to 10000 Pa·s (preferably 20 to 4500 Pa·s, more preferably 50 to 2400 Pa·s).

[0210]

[21] The conductive paste according to any one of

[15] to

[20] , wherein the viscosity of the conductive paste (25° C., shear rate 10 s -1 ) and the viscosity of the conductive paste obtained by a rheometer after storage at 25°C or below for 7 days (25°C, shear rate 10s -1 ) has a viscosity ratio (viscosity after storage / viscosity immediately after mixing) of 10.0 or less.

[0211]

[22] The conductive paste according to any one of

[15] to

[20] , wherein the viscosity of the conductive paste (25° C., shear rate 10 s -1 ) and the viscosity of the conductive paste obtained by a rheometer after storage at 25°C for 7 days (25°C, shear rate 10s -1 ) has a viscosity ratio (viscosity after storage / viscosity immediately after mixing) of 10.0 or less (preferably 0.4 to 5.0, more preferably 0.5 to 3.0).

[0212]

[23] The conductive paste according to any one of

[15] to

[22] , wherein the maximum peak temperature of differential thermogravimetric analysis (DTG) in a nitrogen atmosphere at a heating rate of 10°C / min is 100 to 220°C (preferably 110 to 210°C, more preferably 120 to 200°C).

[0213]

[24] The conductive paste according to any one of

[15] to

[23] , wherein the metal particles are at least one selected from copper particles, silver particles, and particles of oxides thereof.

[0214]

[25] The conductive paste according to any one of

[15] to

[23] , wherein the metal particles are copper particles and / or silver particles.

[0215]

[26] The conductive paste according to

[24] or

[25] , wherein the weight ratio of the copper particles in the entire metal particles (copper particles / total metal particles) is 0.35 to 0.90 (preferably 0.40 to 0.87, more preferably 0.45 to 0.84).

[0216]

[27] The conductive paste according to any one of

[15] to

[26] , wherein the volume average particle size of the metal particles is greater than 1 nm and less than 100 μm (preferably 10 nm to 50 μm, more preferably 30 nm to 35 μm, further preferably 50 nm to 10 μm, and particularly preferably 70 nm to 1 μm).

[0217]

[28] A conductive paste according to any one of

[15] to

[26] , wherein the metal particles are metal particles having two or more different volume average particle sizes selected from nanosized particles (volume average particle size of 1 nm or more and less than 300 nm, preferably 1 to 200 nm, and more preferably 1 to 150 nm), subnanosized particles (volume average particle size of 0.30 μm or more and less than 1.00 μm, preferably 0.40 to 0.95 μm, and more preferably 0.50 to 0.90 μm), and micron-sized particles (volume average particle size of 1.0 to 100 μm, preferably 1.5 to 50 μm, more preferably 2.0 to 35 μm, further preferably 2.5 to 10 μm, and particularly preferably 3.0 to 10 μm).

[0218]

[29] The conductive paste according to

[28] , wherein the weight ratio of the nanosized particles in the entire metal particles (nanosized particles / total metal particles) is 0.10 to 0.90 (preferably 0.15 to 0.85, more preferably 0.20 to 0.80).

[0219]

[30] The conductive paste according to any one of

[15] to

[29] , wherein the content of the metal particles is 70 to 99 wt % (preferably 72 to 95 wt %, more preferably 74 to 93 wt %, further preferably 76 to 95 wt %, particularly preferably 78 to 93 wt %).

[0220]

[31] The conductive paste according to any one of

[15] to

[30] , wherein the content of formic acid is 4.0 to 8.9 wt % (preferably 4.3 to 8.0 wt %, more preferably 4.5 to 7.5 wt %), and the content of the alkaline compound is 6.5 to 12.0 wt % (preferably 6.6 to 11.8 wt %, more preferably 6.7 to 11.5 wt %).

[0221]

[32] The conductive paste according to any one of

[15] to

[31] , wherein the content of the formic acid is 4.0 to 8.9 wt % (preferably 4.3 to 8.0 wt %, more preferably 4.5 to 7.5 wt %), and the weight ratio of the alkaline compound to the formic acid (alkaline compound / formic acid) is 0.70 to 3.50 (preferably 0.72 to 3.40, more preferably 0.74 to 3.30).

[0222]

[33] The conductive paste according to any one of

[15] to

[32] , wherein the content of the alkaline compound is 6.5 to 12.0 wt % (preferably 6.6 to 11.8 wt %, more preferably 6.7 to 11.5 wt %), and the weight ratio of the alkaline compound to the formic acid (alkaline compound / formic acid) is 0.70 to 3.50 (preferably 0.72 to 3.40, more preferably 0.74 to 3.30).

[0223]

[34] A method for producing a conductive paste, which is the method for producing a conductive paste according to any one of

[15] to

[33] , the method comprising the step of mixing the metal particles and the dispersion medium.

[0224]

[35] A use as a dispersion medium for sintering metal particles, wherein the dispersion medium for sintering metal particles is a dispersion medium containing formic acid and the following basic compound.

[0225] Basic compound: a nitrogen-containing compound represented by formula (1).

[0226]

[36] A use as a conductive paste, wherein the conductive paste is a composition comprising metal particles and the following dispersion medium.

[0227] Dispersion medium: contains formic acid and a basic compound, wherein the basic compound is a nitrogen-containing compound represented by formula (1), and the molar ratio of the basic group contained in the basic compound to formic acid (basic group / formic acid) is 0.50 to 1.20.

[0228] Industrial Applicability

[0229] The metal particle sintering dispersion medium disclosed in the present invention can reduce the metal particles and promote sintering even in a non-reducing atmosphere, thereby ensuring the storage stability of the conductive paste and preventing the conductive paste from drying. In addition, the conductive paste disclosed in the present invention can reduce organic residues very little, so it can be sintered even at a low temperature of about 200°C, and can achieve high bonding strength even under a slight pressure of less than 1 MPa. Therefore, the present invention has industrial applicability.

Claims

1. A dispersion medium for sintering metal particles, comprising formic acid and an alkaline compound, The basic compound is a nitrogen-containing compound represented by the following formula (1): In formula (1), R a ~R c are the same or different and represent a hydrogen atom or a hydrocarbon group optionally having a substituent, wherein, R a ~R c are not hydrogen atoms at the same time, and R a ~R c At least one of the following (i) to (iii) is satisfied: (i) is at least one selected from a linear or branched alkyl group having 3 to 12 carbon atoms, a linear or branched alkenyl group, a linear or branched alkynyl group, a linear or branched alkylidene group, a cycloalkyl group and a cycloalkenyl group; (ii) an aromatic hydrocarbon group having 6 to 18 carbon atoms; (iii) is a hydrocarbon group having at least one substituent selected from the group consisting of an amino group, an N-substituted amino group, an N,N-substituted amino group, an imino group, an N-substituted imino group and a hydroxy group, A dotted double line indicates a single bond or a double bond. In the case of a double bond, there is no R. c , R a ~R c Any two of are optionally bonded to each other to form a ring together with the adjacent nitrogen atom, The molar ratio of the basic group contained in the basic compound to formic acid, i.e., basic group / formic acid, is 0.50 to 1.

20. The metal particles are at least one selected from copper particles, copper alloy particles, and copper oxide particles.

2. The dispersion medium for sintering metal particles according to claim 1, wherein The molar ratio, i.e., basic group / formic acid, is 0.55 to 1.

15.

3. The dispersion medium for sintering metal particles according to claim 1, wherein The molar ratio, i.e., basic group / formic acid, is 0.60 to 1.

10.

4. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c It is an aliphatic hydrocarbon group.

5. The dispersion medium for sintering metal particles according to claim 4, wherein The aliphatic hydrocarbon group is a linear or branched alkyl group.

6. The dispersion medium for sintering metal particles according to claim 4, wherein The aliphatic hydrocarbon group is a linear alkyl group having 3 to 12 carbon atoms or a branched alkyl group having 3 to 12 carbon atoms.

7. The dispersion medium for sintering metal particles according to claim 4, wherein The aliphatic hydrocarbon group is a straight-chain alkyl group having 3 to 8 carbon atoms.

8. The dispersion medium for sintering metal particles according to claim 4, wherein The aliphatic hydrocarbon group is a straight-chain alkyl group having 3 to 4 carbon atoms.

9. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the amino group, N-substituted amino group or N,N-substituted amino group which may be present is 0 to 6.

10. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the amino group, N-substituted amino group or N,N-substituted amino group which may be present is 1 to 4.

11. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the amino group, N-substituted amino group or N,N-substituted amino group which may be present is 1 to 2.

12. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the imino group or N-substituted imino group which may be present is 0 to 4.

13. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the imino group or N-substituted imino group which may be present is 1 to 3.

14. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the imino group or N-substituted imino group which may be present is 1 to 2.

15. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the hydroxyl groups which may be present is 0 to 6.

16. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the hydroxyl groups which may be present is 1 to 4.

17. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c The total number of the hydroxyl groups which may be present is 1 to 2.

18. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein In the formula (1), R a ~R c Any two of the rings optionally bonded to each other and formed together with the adjacent nitrogen atom are at least one selected from a pyrrolidine ring, a dihydropyrrole ring, a piperidine ring, a pyrrole ring, an imidazolidine ring, an imidazole ring, a piperazine ring, an imidazolidine ring, a pyridine ring, a diazine ring and a triazine ring.

19. The dispersion medium for sintering metal particles according to claim 18, wherein The ring is an imidazole ring.

20. The dispersion medium for sintering metal particles according to any one of claims 1 to 3, wherein The alkaline compound is at least one compound selected from alkylamines, dialkanolamines, trialkanolamines, aminoalkanediols, diamines, triamines, diaminoalkanols, imidazole compounds, pyridine compounds, diazine compounds and triazine compounds.

21. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein The basic compound is at least one compound selected from the group consisting of alkylamines, dialkanolamines, trialkanolamines, diamines, triamines, diaminoalkanols and imidazole compounds.

22. The metal particle sintering dispersion medium according to any one of claims 1 to 3, wherein The alkaline compound is at least one compound selected from N,N-diethyl-1,3-propylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N'-dimethylpiperazine, 1-(2-aminoethyl)-4-methylpiperazine and N-methylimidazole. 23 . A method for producing a dispersion medium for sintering metal particles, the method comprising the step of mixing the formic acid and the basic compound to make them compatible.

24. A conductive paste comprising metal particles and a dispersion medium for sintering the metal particles, wherein the dispersion medium for sintering the metal particles comprises formic acid and a basic compound. The basic compound is a nitrogen-containing compound represented by the following formula (1): In formula (1), R a ~R c are the same or different and represent a hydrogen atom or a hydrocarbon group optionally having a substituent, wherein, R a ~R c are not hydrogen atoms at the same time, and R a ~R c At least one of the following (i) to (iii) is satisfied: (i) is at least one selected from a linear or branched alkyl group having 3 to 12 carbon atoms, a linear or branched alkenyl group, a linear or branched alkynyl group, a linear or branched alkylidene group, a cycloalkyl group and a cycloalkenyl group; (ii) an aromatic hydrocarbon group having 6 to 18 carbon atoms; (iii) is a hydrocarbon group having at least one substituent selected from the group consisting of an amino group, an N-substituted amino group, an N,N-substituted amino group, an imino group, an N-substituted imino group and a hydroxy group, A dotted double line indicates a single bond or a double bond. In the case of a double bond, there is no R. c , R a ~R c Any two of are optionally bonded to each other to form a ring together with the adjacent nitrogen atom, The molar ratio of the basic group contained in the basic compound to formic acid, ie, basic group / formic acid, is 0.50 to 1.

20.

25. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity is 10 to 1000 Pa·s.

26. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity is 50 to 900 Pa·s.

27. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity is 100-800 Pa·s.

28. The conductive paste according to claim 24, wherein After storage at 25°C for 7 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 4 to 10000 Pa·s.

29. The conductive paste according to claim 24, wherein After storage at 25°C for 7 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 20~4500Pa·s.

30. The conductive paste according to claim 24, wherein After storage at 25°C for 7 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 50 to 2400 Pa·s.

31. The conductive paste according to claim 24, wherein After being stored at 5°C for 7 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 4 to 10000 Pa·s.

32. The conductive paste according to claim 24, wherein After being stored at 5°C for 7 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 20~4500Pa·s.

33. The conductive paste according to claim 24, wherein After being stored at 5°C for 7 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 50 to 2400 Pa·s.

34. The conductive paste according to claim 24, wherein After storage at 25°C for 14 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 4 to 10000 Pa·s.

35. The conductive paste according to claim 24, wherein After storage at 25°C for 14 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 20~4500Pa·s.

36. The conductive paste according to claim 24, wherein After storage at 25°C for 14 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 50 to 2400 Pa·s.

37. The conductive paste according to claim 24, wherein After being stored at 5°C for 14 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 4 to 10000 Pa·s.

38. The conductive paste according to claim 24, wherein After being stored at 5°C for 14 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 20~4500Pa·s.

39. The conductive paste according to claim 24, wherein After being stored at 5°C for 14 days, the rheometer measured the flow rate at 25°C and a shear rate of 10 s. -1 The viscosity is 50 to 2400 Pa·s.

40. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity at 25°C and the viscosity at 10s shear rate obtained by rheometer after storage at 25°C or below for 7 days -1 The viscosity ratio of the viscosity after storage / the viscosity immediately after mixing is 10.0 or less.

41. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity at 25°C and the viscosity at 10 s after storage at 25°C for 7 days were measured by a rheometer. -1 The viscosity ratio of the viscosity after storage / the viscosity immediately after mixing is 10.0 or less.

42. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity at 25°C and the viscosity at 10 s after storage at 25°C for 7 days were measured by a rheometer. -1 The viscosity ratio of the viscosity after storage / viscosity immediately after mixing is 0.4 to 5.

0.

43. The conductive paste according to claim 24, wherein The dispersion medium and the metal particles were immediately mixed and the shear rate was measured by a rheometer at 25°C and 10 s. -1 The viscosity at 25°C and the viscosity at 10 s after storage at 25°C for 7 days were measured by a rheometer. -1 The viscosity ratio of the viscosity after storage / viscosity immediately after mixing is 0.5 to 3.

0.

44. The conductive paste according to claim 24, wherein The maximum peak temperature of differential thermogravimetric analysis (DTG) in a nitrogen atmosphere at a heating rate of 10°C / min was 100 to 220°C.

45. The conductive paste according to claim 24, wherein The maximum peak temperature of differential thermogravimetric analysis (DTG) in a nitrogen atmosphere at a heating rate of 10°C / min was 110 to 210°C.

46. ​​The conductive paste according to claim 24, wherein The maximum peak temperature of differential thermogravimetric analysis (DTG) in a nitrogen atmosphere at a heating rate of 10°C / min was 120 to 200°C.

47. The conductive paste according to claim 24, wherein The metal particles are at least one selected from copper particles, silver particles, and particles of oxides thereof.

48. The conductive paste according to claim 24, wherein The metal particles are copper particles and / or silver particles.

49. The conductive paste according to claim 24, wherein The volume average particle size of the metal particles is 1 nm or more and 100 μm or less.

50. The conductive paste according to claim 47, wherein The weight ratio of the copper particles in the entire metal particles, that is, copper particles / the entire metal particles, is 0.35 to 0.

90.

51. The conductive paste according to claim 47, wherein The weight ratio of the copper particles in the entire metal particles, that is, copper particles / the entire metal particles, is 0.40 to 0.

87.

52. The conductive paste according to claim 47, wherein The weight ratio of the copper particles in the entire metal particles, that is, copper particles / the entire metal particles, is 0.45 to 0.

84.

53. The conductive paste according to claim 24, wherein The volume average particle size of the metal particles is 10 nm to 50 μm.

54. The conductive paste according to claim 24, wherein The volume average particle size of the metal particles is 30 nm to 35 μm.

55. The conductive paste according to claim 24, wherein The volume average particle size of the metal particles is 50 nm to 10 μm.

56. The conductive paste according to claim 24, wherein The volume average particle size of the metal particles is 70 nm to 1 μm.

57. The conductive paste according to claim 24, wherein The metal particles are composed of two or more metal particles with different volume average particle sizes selected from nano-sized particles with a volume average particle size of 1 nm or more and less than 300 nm, sub-nano-sized particles with a volume average particle size of 0.30 μm or more and less than 1.00 μm, and micron-sized particles with a volume average particle size of 1.0 to 100 μm.

58. The conductive paste according to claim 24, wherein The metal particles are two or more metal particles with different volume average particle sizes selected from nano-sized particles with a volume average particle size of 1 to 200 nm, sub-nano-sized particles with a volume average particle size of 0.40 to 0.95 μm, and micron-sized particles with a volume average particle size of 2.0 to 35 μm.

59. The conductive paste according to claim 24, wherein The metal particles are two or more metal particles with different volume average particle sizes selected from nano-sized particles with a volume average particle size of 1 to 150 nm, sub-nano-sized particles with a volume average particle size of 0.50 to 0.90 μm, and micron-sized particles with a volume average particle size of 3.0 to 10 μm.

60. The conductive paste according to claim 57, wherein The weight ratio of the nanosized particles to the entire metal particles, that is, nanosized particles / entire metal particles, is 0.10 to 0.

90.

61. The conductive paste according to claim 57, wherein The weight ratio of the nanosized particles to the entire metal particles, that is, nanosized particles / entire metal particles, is 0.15 to 0.

85.

62. The conductive paste according to claim 57, wherein The weight ratio of the nanosized particles to the entire metal particles, that is, nanosized particles / entire metal particles, is 0.20 to 0.

80.

63. The conductive paste according to any one of claims 24 to 62, wherein The content of the metal particles is 70 to 99% by weight.

64. The conductive paste according to any one of claims 24 to 62, wherein The content of the metal particles is 72 to 95% by weight.

65. The conductive paste according to any one of claims 24 to 62, wherein The content of the metal particles is 74 to 93% by weight.

66. The conductive paste according to any one of claims 24 to 62, wherein The content of the metal particles is 78 to 93% by weight.

67. The conductive paste according to any one of claims 24 to 62, wherein The content of the formic acid is 4.0 to 8.9% by weight, and the content of the basic compound is 6.5 to 12.0% by weight.

68. The conductive paste according to any one of claims 24 to 62, wherein The content of the formic acid is 4.3-8.0% by weight, and the content of the basic compound is 6.6-1.8% by weight.

69. The conductive paste according to any one of claims 24 to 62, wherein The content of the formic acid is 4.5-7.5% by weight, and the content of the basic compound is 6.7-11.5% by weight.

70. The conductive paste according to any one of claims 24 to 62, wherein The content of the formic acid is 4.0 to 8.9% by weight, and the weight ratio of the alkaline compound to the formic acid, ie, the alkaline compound / formic acid, is 0.70 to 3.

50.

71. The conductive paste according to any one of claims 24 to 62, wherein The content of the formic acid is 4.3-8.0% by weight, and the weight ratio of the alkaline compound to the formic acid, ie, the alkaline compound / formic acid, is 0.72-3.

40.

72. The conductive paste according to any one of claims 24 to 62, wherein The content of the formic acid is 4.5-7.5% by weight, and the weight ratio of the alkaline compound to the formic acid, ie, the alkaline compound / formic acid, is 0.74-3.

30.

73. The conductive paste according to any one of claims 24 to 62, wherein The content of the alkaline compound is 6.5-12.0% by weight, and the weight ratio of the alkaline compound to the formic acid, ie, the alkaline compound / formic acid, is 0.70-3.

50.

74. The conductive paste according to any one of claims 24 to 62, wherein The content of the alkaline compound is 6.6-11.8% by weight, and the weight ratio of the alkaline compound to the formic acid, ie, the alkaline compound / formic acid, is 0.72-3.

40.

75. The conductive paste according to any one of claims 24 to 62, wherein The content of the alkaline compound is 6.7-11.5% by weight, and the weight ratio of the alkaline compound to the formic acid, ie, the alkaline compound / formic acid, is 0.74-3.

30.

76. A sintered body, which is a sintered body of the conductive paste according to any one of claims 24 to 75.

77. An electronic device comprising a sintered body of the conductive paste according to any one of claims 24 to 75 on a substrate.

78. A use as a dispersion medium for sintering metal particles, wherein: The metal particle sintering dispersion medium comprises formic acid and a basic compound, The basic compound is a nitrogen-containing compound represented by the following formula (1): In formula (1), R a ~R c are the same or different and represent a hydrogen atom or a hydrocarbon group optionally having a substituent, wherein R a ~R c are not hydrogen atoms at the same time, and R a ~R c At least one of the following (i) to (iii) is satisfied: (i) is at least one selected from a linear or branched alkyl group having 3 to 12 carbon atoms, a linear or branched alkenyl group, a linear or branched alkynyl group, a linear or branched alkylidene group, a cycloalkyl group and a cycloalkenyl group; (ii) an aromatic hydrocarbon group having 6 to 18 carbon atoms; (iii) is a hydrocarbon group having at least one substituent selected from the group consisting of an amino group, an N-substituted amino group, an N,N-substituted amino group, an imino group, an N-substituted imino group and a hydroxy group, A dotted double line indicates a single bond or a double bond. In the case of a double bond, there is no R. c , R a ~R c Any two of are optionally bonded to each other to form a ring together with the adjacent nitrogen atom, The molar ratio of the basic group contained in the basic compound to formic acid, ie, basic group / formic acid, is 0.50 to 1.20.

Citation Information

Patent Citations

  • Copper paste for bonding, bonded body and manufacturing method thereof, and semiconductor device and manufacturing method thereof

    JP2018156736A

  • Conductor-forming composition, and joint body, and method for producing the same

    JP2018170228A

  • Game machine

    JP2020025765A

  • Bonding device

    WO2018029983A1

  • Environment-friendly conductive silver paste

    CN104538085A